Combined Therapy Versus Usual Care in the Treatment of Depressed Cancer Patients with Pain - Bovero, Andrea; Ieraci, Valentina; Amodeo, Laura; Malabaila, Alice; Ferrero, Andrea; Torta, Riccardo (International Journal of Psychotherapy Practice and Research, 2017)
Objective To compare Brief Adlerian Psychodynamic Psychotherapy (B-APP) plus venlafaxine versus venlafaxine plus usual care on pain and depressive symptomatology of depressed patients with cancer pain. Methods A total of 100 patients with pain and mood depression, according to DSM IV-TR, were randomized to receive treatment with B-APP plus venlafaxine (n=51) or venlafaxine plus usual care (n=49). The sample was evaluated at baseline and after 10 weeks with the Visual Analogue Scale (VAS); the Hospital Anxiety Depression Scale (HADS); the Montgomery Asberg Depression Rating Scale (MADRS); the Clinical Global Impressions (CGI); the Mini-Mental Adjustment to Cancer Scale (Mini-MAC); the European Organization for Research and Treatment of Cancer Quality-of Life Questionnaire (EORTC QLQ-C30) and the Dosage Record and Treatment Emergent Symptom scale (DOTES). Only at the endpoint was the Verona Service Satisfaction Scale (VSSS-54) also administered. Results A significant reduction in VAS and HADS scores was observed in both treatments, but a higher significance (p<0.01) was present only in subjects also treated with psychotherapy. A significant change was obtained in Mini-MAC scores (p<0.01) for Fighting Spirit, Fatalism, Anxious Preoccupation (p<0.01) and Avoidance items (p<0.05) only in patients treated with combined therapy. The combined group also showed more satisfaction with the treatment in their responses to the VSSS-54. Conclusions Brief Adlerian Psychodynamic Psychotherapy (B-APP) in combination with venlafaxine was superior to usual care and venlafaxine in improving depressive symptomatology and reducing pain.
Keywords: cancer; pain; depression; combined therapy; psychotherapy